2021
DOI: 10.1097/nmd.0000000000001389
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Mitigation Efforts on Adults With Serious Mental Illness

Abstract: In response to COVID-19 mitigation policies, mental health and social service agencies have had to rapidly change their operations, creating challenges for patients with serious mental illness (SMI). This study aimed to explore the experiences of adults with SMI navigating these altered systems during the pandemic. In-depth interviews were conducted with 20 hospitalized adults with SMI in the fall of 2020; they were coded using thematic analysis. Most participants found the new systems effective at meeting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“… 9 In addition, a study examining the impact of the COVID-19 pandemic on adults with serious mental illness found that of the 20 adults interviewed in their study, several indicated an inability to access mental health care and public health benefits. 10 …”
Section: Introductionmentioning
confidence: 99%
“… 9 In addition, a study examining the impact of the COVID-19 pandemic on adults with serious mental illness found that of the 20 adults interviewed in their study, several indicated an inability to access mental health care and public health benefits. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Evidence of negative impacts of lockdown on people with existing MHCs and the adequacy of mental health services were reported from Switzerland [17], Italy [18] and Norway [17]. Reductions in the availability and quality of mental health services were reported from Spain [19] and significant unmet needs of service users, including inability to access welfare benefits were reported in the USA [20]. General adverse impacts of the pandemic were also reported: in Sweden 20% of people with pre-existing MHCs reported an increase in their psychiatric medication compared to pre- pandemic [21].…”
Section: Introductionmentioning
confidence: 99%